System-Wide Analysis of Electric Power System for a Reference Short-Range Electrified Aircraft - Ahmad Naderi; Robert Keilmann; Arsham Asgari; Abbas Mehraban; Regine Mallwitz; Markus Henke; Michael Terorde (IEEE Access)
This study investigates the electrification of a reference short-range passenger aircraft, focusing on optimizing the Electric Power System (EPS). An iterative optimization method is employed to identify the optimal specifications for individual EPS components, considering gravimetric and volumetric power densities and efficiency as single objectives. The study introduces a structured, decoupled optimization framework that isolates the impact of each design variable on weight, volume, and efficiency, providing clearer insights into system-level trade-offs and offering a novel perspective for EPS design. By incorporating component characteristics into the design process, optimal configurations are achieved. Results indicate that certain motor designs enhance EPS performance by reducing weight, increasing efficiency, or minimizing volume, depending on the optimization objective. Similarly, during the optimization process and selection of power electronics configurations, certain topologies demonstrated superior efficiency, while others excelled in different performance criteria. In transmission line selection, superconducting cables are more efficient than conventional cables in minimizing electrical losses at lower voltages, despite being bulkier. Conversely, conventional cables are more advantageous at higher voltage levels due to their lighter weight. Moreover, modular and scalable circuit breakers are recommended for their adaptability across varying voltage levels. The optimization results are further supported by sensitivity analyses that reveal the influence of voltage level, shaft power, and cable technology on overall system metrics. Additionally, feasibility assessments benchmarked against a conventional ATR-72 propulsion system highlight the current limitations of battery integration and the challenging energy density requirements for full electrification.